Artificial Intelligence in Internal Auditing: Enhancing Decision-Making and Audit Quality in the Saudi Accounting Sector - Hassan Salah Anwer Ghozi (Decision Making: Applications in Management and Engineering, 2024)
This study delves into the impact of artificial intelligence (AI) on internal auditing within the accounting sector, utilizing descriptive analysis to provide a comprehensive understanding. We meticulously designed and administered a structured questionnaire for 73 participants, including both internal and external auditors and financial managers. The questionnaire aimed to evaluate current AI utilization, potential benefits, implementation challenges, and effective strategies for AI adoption. The findings reveal a substantial gap between the anticipated and actual use of AI in internal auditing. Only 64% of these organizations currently employ AI technologies, despite 72.9% of respondents believing that the industry will soon widely adopt AI. AI has demonstrated the potential to reduce audit time by 30–40% and significantly enhance the accuracy of risk assessments by 50–60%. However, various challenges, such as concerns over data security (76.7%), a shortage of qualified professional staff (74.9%), and inadequate technological support (76.2%), impede the path to full AI adoption. The study underscores the pressing need for clear, well-defined, and strategic implementation plans to effectively integrate AI into auditing practices. Future efforts should prioritize optimizing the synergy between AI capabilities and human expertise, which could lead to improved audit quality by 30–40%.